Bacillus pumilus SE5 originated PG and LTA tuned the intestinal TLRs/MyD88 signaling and microbiota in grouper (Epinephelus coioides). Issue 88 (May 2019) - Yang, Hong-Ling; Sun, Yun-Zhang; Hu, Xi; Ye, Ji-dan; Lu, Kang-Le; Hu, Ling-Hao; Zhang, Jiao-Jing
Abstract: The normal microbiota plays a key role in the health of host, but little is known of how the fish immune system recognizes and responds to indigenous bacteria/probiotics. Our previous studies have showed that heat-inactivated indigenous Bacillus pumilus SE5 activate the TLR2 signaling pathways and modulate the intestinal microbiota in grouper ( Epinephelus coioides ), suggesting microbial-associated molecular patterns (MAMPs) involved. In this study, whole cell wall (CW) and two possible MAMPs, peptidoglycan (PG) and lipoteichoic acid (LTA) have been extracted from B. pumilus SE5 and their effects on intestinal immune related genes expression and microbiota were evaluated in a 60 days feeding trial. Significantly elevated expression of TLR1, TLR2, TLR5 and MyD88 was observed in fish fed the CW, PG and LTA containing diets, and the highest expression was observed in groups PG and LTA. At the same time, significantly upregulated expression of antimicrobial effectors, such as antimicrobial peptides (epinecidin-1, hepcidin-1 and β-defensin), C-type Lectin and IgM was observed in fish fed PG and LTA containing diets. This induced activation of intestinal immunity was consistent with the microbiota data showing that CW, PG and LTA originated from SE5 modulated the overall structure of intestinal microbiota, and the relative abundance of potentially pathogenic Vibrio decreased significantly while beneficial Lactobacillus increased significantly in fish fed PG and LTA. In conclusion, both the PG and LTA originated from B. pumilus SE5 could activate TLRs/MyD88 signaling and expression of wide-ranging antibacterial effectors, and therefore shape the intestinal microbiota in grouper. Highlights: Both the PG and LTA originated from B. pumilus SE5 shape the intestinal microbiota. TLRs/MyD88 signaling involved in probiotic PG and LTA recognition. PG and LTA shape intestinal immunity and microbiota.